Technological and marketing evaluation of solar panel cleaning robots - Dornas, Victor Seabra; Ghesti, Grace Ferreira; Gomes, André Rogério Silva; Portella, Carlos Eduardo Parucker; Guedes, Daniel Mendes (Seven Editora, 2024)
This article aims to analyze the degree of innovation and viability of technologies that use autonomous robots to clean photovoltaic panels, also known as solar panels. How do they work and what would be the relevance of these features in tropical countries like Brazil? The current scenario is one of protagonism for the so-called energy transitions, that is, new ways of using energy aiming at independence from the use of non-renewable sources, such as fossil fuels (oil, coal and natural gas). As a result, there is a gradual increase in investment in technological development sectors that enable renewable sources (solar, wind, hydroelectric, geothermal and biomass), even in countries like Brazil that are still late in the transition. The present study analyzes a specific technology to improve the functioning of photovoltaic panels with the use of autonomous cleaning robots that do not use too much force or pressure that harms the anti-reflective surface of the panels. This is a type of innovation that has been increasingly discussed in the Brazilian scenario, as it improves product lines that are still in the market absorption phase. Therefore, the study analyzes a patent on autonomous robots that perform cleaning functions without the use of water. The study investigates whether these products are viable technology in the Brazilian market. We also seek to analyze the technological transfer of protected or unprotected assets as an internationalization strategy. DOI:https://doi.org/10.56238/sevened2023.006-125